Bark-inhabiting fungal communities of European chestnut undergo substantial alteration by canker formation following chestnut blight infection - Douanla-Meli, Clovis; Moll, Julia (Frontiers in Microbiology, 2023)
Chestnut forests are severely threatened by chestnut blight caused by the fungal pathogen Cryphonectria parasitica. Infected trees exhibit bark discoloration and canker formation. To explore whether and how chestnut blight is reflected in bark-inhabiting fungal communities of European chestnut (Castanea sativa), we used amplicon sequencing of the ITS2 region of rDNA of samples from asymptomatic trees, asymptomatic trees with latent C. parasitica infection, and infected trees with canker tissues. We further assessed the co-occurrence of C. parasitica and Gnomoniopsis smithogilvyi, another canker-causing fungal pathogen of European chestnut. Fungal community composition and diversity differed between the sample types. The fungal community composition was substantially reshaped by canker formation, whereas latent C. parasitica infection and more specifically pre-canker infection period per se had a weak effect. C. parasitica greatly dominated the mycobiome of canker samples, whereas G. smithogilvyi was found in only 9% of canker samples at very low abundances. However, G. smithogilvyi was the dominant fungus in the bark of healthy plants. This study highlights that mycobiome alteration in the bark tissues of European chestnut is ascribed to canker formation due to C. parasitica infection. This further emphasizes the scarce co-occurrence of C. parasitica and G. smithogilvyi on European chestnut.